Mesenchymal Stem Cell Secretome Improves Bone Quality in Autoimmune Rheumatic Patients (AIIRD): A Case Report - Werdiningsih, Yulyani; Nurudhin, Arief; sunarso, indrayana (Indonesian Basic and Experimental Health Sciences, 2024)
ABSTRAK Autoimmune Inflammatory Rheumatic Disease (AIIRD) is a group of different disorders, which have similar clinical, laboratory and immunological manifestations. In East Asia, the top 3 diseases included in AIIRD are Systemic Lupus Erythematosus, Rheumatoid Arthritis, and Sjogren's Syndrome. Glucocorticoids are still one of the therapeutic modalities for AIIIRD with their antiinflammatory and immunosuppressive effects. However, glucocorticoids have some side effects. One side effect of concern is decreased bone density. The condition of glucocorticoid induced osteoporosis (GIOP) is reported with increasing prevalence. The main effect of the use of glucocorticoids on bones is the presence of impaired bone formation regardless of the role of inflammation.  Secretome stem cells contain bioactives that exhibit diverse physiological functions such as immunomodulation, anti-inflammatory, angiogenesis, anti-apoptotic and anti-oxidation. Secretome can modulate cell differentiation by promoting osteogenesis and inhibiting adipogenesis. In this case report, it showed improvements in markers of bone damage, inflamation, and vitamin D levels after stem cell secretome administration in AIIRD patients with long-term corticosteroid use.